2019
DOI: 10.2109/jcersj2.19022
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-ion conductivity and crystal structure of garnet-type solid electrolyte Li<sub>7−</sub><i><sub>x</sub></i>La<sub>3</sub>Zr<sub>2−</sub><i><sub>x</sub></i>Ta<i><sub>x</sub></i>O<sub>12</sub> using single-crystal

Abstract: Single-crystal rods of Li 7¹x La 3 Zr 2¹x Ta x O 12 (X = 0.2, 0.4, 0.5, 0.6, 0.8) were grown by floating zone melting. The typical size of the single-crystal rod was 8 mm in diameter and 70 mm in length. Li 7¹x La 3 Zr 2¹x Ta x O 12 (X = 0.2, 0.4, 0.5, 0.6, 0.8) crystallizes in a cubic structure with an Ia-3d space group. Single crystal structure analysis was performed for all single crystals. How the lithium ion conductivity varies with the substitution amount of tantalum was investigated using a single cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
0
25
1
Order By: Relevance
“…5b shows calculated lattice parameters at room temperature as a function of x (Li content) in Li x La 3 Zr x −5 Ta 7− x O 12 . The experimental data of single crystals from Kataoka et al , 10 Al-free powder samples from Buschmann et al , 39 Matsuda et al , 6 Awaka et al , 8 and Thompson et al 40 are shown in the plot for comparison. For cubic phases, the lattice parameter increases linearly with increasing Li content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5b shows calculated lattice parameters at room temperature as a function of x (Li content) in Li x La 3 Zr x −5 Ta 7− x O 12 . The experimental data of single crystals from Kataoka et al , 10 Al-free powder samples from Buschmann et al , 39 Matsuda et al , 6 Awaka et al , 8 and Thompson et al 40 are shown in the plot for comparison. For cubic phases, the lattice parameter increases linearly with increasing Li content.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Buschmann et al , 6 Inada et al , 7 Matsuda et al 8 and Yi et al 9 synthesized Al-free compositions of Li x La 3 Zr x −5 Ta 7− x O 12 and found that ionic conductivity reaches a maximum at x = 6 (2.6 × 10 −4 S cm −1 ), x = 6.5 (6.1 × 10 −4 S cm −1 ), x = 6.6 (4.7 × 10 −4 S cm −1 ), and x = 6.7 (1.03 × 10 −3 S cm −1 ), respectively. Furthermore, Kataoka et al 10 synthesized single crystals and found that x = 6.6 has the highest ionic conductivity of 1.1 × 10 −3 S cm −1 . Thus, it appears that it is controversial as to what is the composition for the maximum conductivity in Li x La 3 Zr x −5 Ta 7− x O 12 even in Al-free samples.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our 1×‐SSR 1000 sample shows comparable ionic conductivity to samples prepared with the aforementioned methods, implying that a single reaction at a higher temperature may be an attractive strategy to minimize the number of synthesis steps. Another option is single crystal growth from an appropriate melt (see Table S1, Supporting Information, Kataoka and Akimoto [ 34,35 ] ). While the energy cost of each of these approaches is quite high, they can produce garnet electrolytes with very high ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1,3,7–10 ] Many doping schemes have been explored, including Al 3+ [ 6,7,11 ] and Ga 3+ [ 7,12 ] to dope the Li sublattice, Nb 5+ [ 13,14 ] and Ta 5+ [ 7–9,14–28 ] to dope the Zr sublattice, Ca 2+ [ 22,29 ] and other alkaline earths such as Ba 2+ [ 30 ] to dope the La sublattice (often used in conjunction with another site dopant), and even recently F − [ 31–33 ] to dope the oxygen sublattice. Of the many possible compositions of LLZO, Ta‐doped LLZO (LLZTO) with formula Li 7− x La 3 Zr 2− x Ta x O 12 (0.2 < x < 1) combines good electrochemical stability with lithium metal [ 14 ] and high ionic conductivity (>1 mS cm −1 ) [ 23,34,35 ] and, by virtue of doping the Zr sites in the garnet structure, does not block sites on the Li sublattice [ 7 ] unlike other dopants such as Al or Ga.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation